Cost-effectiveness Analysis Of Biologic Sequential Treatments For Moderate-to-severe Psoriasis: A Malaysian Healthcare System Perspective - Nor Azmaniza Azizam; Mofakhar Hussain; Eric Nauenberg; Wei Chern Ang; Amirah Azzeri; Jacob Smith (Plos, 2024)
Indexed by WOS/Scopus/ERA